Psychology as a Basis for Islamic Education Curriculum Development - Teguh Hadi Wibowo; Tobroni Tobroni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The aim of this study is to explore how psychological principles can serve as a basis for creating a more effective and relevant Islamic education curriculum that meets students’ needs at various developmental stages. The study employed a qualitative approach, utilizing library research as its methodological framework. Data were sourced from reputable scholarly literature, and content analysis techniques were applied to ensure the validity and reliability of the findings. The study reveals that Islamic education curriculum development is a complex process requiring a comprehensive understanding of various educational theories and principles. This research identifies a five-step model for curriculum development: (1) performing a goal-and-objective analysis, (2) selecting appropriate approaches, (3) organizing and prioritizing the material, (4) implementing the curriculum, and (5) evaluating the curriculum. A solid foundational basis is essential to guide educators and stakeholders in applying the curriculum effectively. Psychology, particularly developmental and educational psychology, offers valuable insights for designing instructional strategies aligned with students’ cognitive, emotional, and social development. The curriculum should ensure holistic student growth, include both core and elective subjects, and foster meaningful teacher-student interactions. This research contributes to the academic discourse by addressing a gap in existing literature, which often neglects the psychological perspective in Islamic education curriculum design. By proposing a theoretical framework grounded in psychological principles, the study offers a foundation for future empirical research and practical applications. It supports the development of curriculum that are not only academically rigorous but also responsive to the individual development of learners in Islamic educational contexts.